Pengembangan Pembelajaran Pendidikan Lingkungan Berbasis Outdoor Untuk Calon Guru Sekolah Dasar - Amini, Risda (2005)
Studi tentang pengembangan model pembelajaran Pendidikan Lingkungan berbasis Outdoor (PLO) berfokus pada permasalahan lingkungan sekolah, dimaksudkan untuk meningkatkan kemampuan dasar calon guru SD. Model PLO yang dikembangkan mengkaji permasalahan lingkungan sekolah; menggunakan fasilitas belajar yang ada di luar/dalam kelas sebagai sumber belajar; serta pembelajaran menekankan pada pengembangan sikap/perilaku peduli terhadap lingkungan sekolah. Penelitian ini menggunakan desain Research and Development dengan subyek penelitian mahasiswa PGSD sebanyak 37 orang pada kelas eksperimen dan 47 orang pada kelas kontrol. Dalam implementasi model dilakukan percobaan di luar kelas dan pemanfaatan video pembelajaran. Penelitian ini menghasilkan: 1) Model PLO yang membekali calon guru merancang pembelajaran IPA dengan mengintegrasikan materi yang membahas permasalahan lingkungan sekolah, melaksanakan pembelajaran dengan menggunakan model PLO berbasis lingkungan sekolah, dan evaluasi pembelajaran yang menekankan pada pengembangan sikap/perilaku peduli lingkungan; 2) Peningkatan kemampuan dasar calon guru; 3) Peningkatan sikap dan perilaku peduli lingkungan sekolah. Model PLO efektif ditinjau dari: 1) penguasaan konsep pendidikan lingkungan termasuk kategori baik; 2) peningkatan penguasaan konsep termasuk kategori sedang (Ng = 0,59); 3) kinerja dan sikap melakukan percobaan termasuk kategori sangat baik; 4) kemampuan dalam pembelajaran termasuk kategori baik; dan 5) sikap dan perilaku terhadap lingkungan sekolah termasuk kategori sangat peduli (Ng = 0,31). Keunggulan model PLO diantaranya meningkatkan kemampuan calon guru dalam menanamkan sikap/perilaku peduli lingkungan. Keterbatasan model PLO adalah menuntut kemampuan calon guru mengintegrasikan materi pendidikan lingkungan ke dalam mata pelajaran IPA. ABSTRACT The study of outdoor based-instruction model development for environmental education which called PLO focused on the school environmental problems, its purposed to improve pre-service teachers' ability. The PLO concerned for solving the environmental problem in school surrounding; using facilities in outdoor place as learning sources; and providing knowledge, skills, and attitude to the environment as major priority. This research used Research and Development with pre-test and post-test one group design for piloting study, whereas for model testing using pretest-posttest control group design in term of quasi experiment method. As subjects were pre-service teachers in the elementary school including 37 students for experiment and 47 students for control class. Implementing PLO was carried out through an outdoor experiment and presented by an instructional video. The data collected were interview, observation sheets, performance assessment sheets, attitude questionnaires, and tests. This current research revealed that: 1) the outdoor based-instructional model supplies to pre-service teachers for designing lesson plan, conducting science learning process by the implementation the PLO model and evaluating the learning process by putting an emphasis, 2) the improvement of the pre-service teachers' basic skills, 3) the improvement attitude toward the school environment. The effectiveness of the PLO are: 1) the pre-service teachers' mastery of environmental education concepts was categorized as good, 2) the improvement of the pre-service teachers' mastery of environmental education concepts was categorized as medium (Ng = 0,59), 3) the pre-service teachers performance and attitude in the experiment class was categorized as high level, 4) the pre-service teachers' ability was categorized as good, 5) the attitude and behavior about the school environment was categorized extremely care (Ng = 0,31). One of the benefits of PLO is that it can improve teachers' capacity on solving problems in the school. However this research need teachers to have abilities in integrating environmental education into science teaching in elementary school.